2008
DOI: 10.1111/j.1365-4632.2008.03783.x
|View full text |Cite
|
Sign up to set email alerts
|

Hair growth stimulatory effect by a combination of 5‐aminolevulinic acid and iron ion

Abstract: The results suggest that an admixture of 5-ALA and iron ion stimulates murine hair growth in vivo independent of epithelial and mesenchymal cells, although the precise mechanism is still uncertain. This mixture has the potential to become a beneficial new treatment for alopecia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
(31 reference statements)
1
17
0
Order By: Relevance
“…Wang et al demonstrated that ALA and vitamin C supplementation improved iron status including hemoglobin levels in sows and laying hens [24,25]. Yamazaki et al revealed that ALA and iron ion administration caused a stimulatory effect on hair growth [26]. These findings strongly suggest that ALA is a potentially useful nutritional supplement.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al demonstrated that ALA and vitamin C supplementation improved iron status including hemoglobin levels in sows and laying hens [24,25]. Yamazaki et al revealed that ALA and iron ion administration caused a stimulatory effect on hair growth [26]. These findings strongly suggest that ALA is a potentially useful nutritional supplement.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, ALA at lower doses than those used for PDD and PDT (20 mg/kg), may help to prevent and treat chronic diseases via activation of the electron transport system for heme homeostasis in mitochondria. [20] The use of ALA phosphate at a lower dose (mg/M 2 ), in combination with ferrous citrates to prevent phototoxicity, might also have cosmetic applications for conditions, such as alopecia, [21] anti-aging supplements and improved lipid metabolism (Fig. 1).…”
Section: What Is Ala?mentioning
confidence: 99%
“…Hence, as the precursor of heme, ALA is an essential molecule in human and other vertebrates, and may be associated with various metabolic disorders. Indeed, it has been reported that the administration of ALA together with iron stimulates murine hair growth [4].…”
Section: Introductionmentioning
confidence: 99%